2013
DOI: 10.1186/2229-0443-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Organization of ideas in writing: what are raters sensitive to?

Abstract: Whether foreign language writing is rated using analytic rating scales or holistically, the organization of ideas is invariably one of the aspects assessed. However, it is unclear what raters are sensitive to when rating writing for organization. Which do they value more highly, the physical aspects of organization, such as paragraphing and the existence of organization markers, or deeper textual aspects, such as the coherent flow of ideas? This study investigates whether raters of timed essays value paragraph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Students in experimental group showed a better content organization. In writing, a good content organization will make a good flow writing so that readers will more easily grasp the message (Ruegg & Sugiyama, 2013;Tosuncuoğlu, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Students in experimental group showed a better content organization. In writing, a good content organization will make a good flow writing so that readers will more easily grasp the message (Ruegg & Sugiyama, 2013;Tosuncuoğlu, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers from this study confirmed the importance of its effects in attracting readers ' attention and interest. They train students to pay attention to their writing with introductory sentences supported by explanatory sentences and end with a cover [8].…”
Section: Coherence Errorsmentioning
confidence: 99%
“…The researcher was able to elicit from the participants that engagement with discussing a novel was 'more "substantial" than simply answering grammar questions '. Erdosy (2004) in Ruegg and Sugiyama (2013) applied think-aloud protocols to compare the assessment performance of four raters on a TOEFL exam. Similarly, MacIntyre 2007in Ruegg and Sugiyama (2013 p.3)conducted think-aloud protocols to find out if the grading scale that was based on an analytic framework proved reliable in assessing writing.…”
Section: Collocation Collocationmentioning
confidence: 99%